Features of the course of primary and recurrent herpetic keratitis developing following COVID-19 vaccination - K.V. Sereda; G.I. Drozhzhyna; N.I. Khramenko (Journal of Ophthalmology, 2025)
Purpose: To assess the features of the course of primary and recurrent herpetic keratitis (HK) developing following COVID-19 vaccination.